Some New Aspects in the Structure and Functional Activity of Sea Anemone Neurotoxins - Margarita Monastyrnaya; Rimma Kalina; Emma Kozlovskaya (Novel Aspects on Chemistry and Biochemistry Vol. 6, 2023)
The aim of this work was to summarize the literature and our own experimental data obtained over the past four decades on the structure-functional relationships of all sea anemone neurotoxins described to date, specifically interacting with various subtypes of voltage-gated sodium channels (VGSCs/NaVs). Disruption of the functional activity of these biological targets causes many severe pathologies, while natural toxins, including those of sea anemones, may prove to be a promising tool in pharmacological research, as well as in the study of the molecular organization and mechanisms of NaVs functioning. The review also focuses on the several type 2 neurotoxins from the sea anemone Heteractis crispa, five structurally homologous, and one unique double-chain neurotoxin that we first identified in sea anemones. Due to the loss of the functionally significant Arg14 residue, this peptide homolog of the remaining Heteractis neurotoxins completely lost its toxicity, but retained the ability to modulate several subtypes of NaVs, which is characteristic of type 2 neurotoxins. The review discusses the results of in vivo, in vitro, and in silico studies of the interaction of neurotoxins with their biological targets, sodium channels of several NaV subtypes.